Genetic Variants and Disease Mechanisms: Lessons from Monogenic Childhood Epilepsies - Oberlack, Ava; Wagner, Matias (Neuropediatrics, 2025)
The elucidation of the molecular basis of monogenic epilepsies is advancing rapidly. For clinicians, knowing not only the affected gene, but also the patient's exact genetic variant and gaining insight into its effect on RNA, protein, cell, and organism level is becoming increasingly important. As different variants in the same gene can lead to opposing functional effects, an understanding of their nature is crucial for informed treatment choices. Correctly counseling patients, parents, and families regarding the patient's prognosis and the risk to other family members of being affected or having an affected child is only possible with detailed knowledge of the genetic and functional alterations underlying the condition. This review aims to provide a comprehensive overview of genetic variants and their effects, following them from the DNA to the organism level. Protein-level outcomes, such as gain- and loss-of-function mechanisms as well as dominant-negative effects, will be illustrated using examples from monogenic epilepsies. Their downstream impact on cellular function and phenotype will be traced to shed light on the mechanisms by which different variants in the same gene can result in diverging clinical presentations. In doing so, we illustrate key genetic concepts relevant to clinical practice to help inform clinical interpretation of genetic variants and facilitate therapeutic decision-making.
Keywords: monogenic epilepsy; genetic variants; variant effects; gain-of-function; dominant-negative; loss-of-function